Clinicopathological characteristics of posttransplant lymphoproliferative disorders of T-cell origin: single-center series of nine cases and meta-analysis of 147 reported cases. Issue 10 (October 2013) - Herreman, An; Dierickx, Daan; Morscio, Julie; Camps, Jordi; Bittoun, Emilie; Verhoef, Gregor; De Wolf-Peeters, Christiane; Sagaert, Xavier; Tousseyn, Thomas
Abstract T-cell or natural killer (NK)-cell posttransplant lymphoproliferative disorder (T-PTLD) is a rare but severe complication after transplant. Here we present the clinicopathological features of a single-center series of nine cases. Additionally, we summarize the clinicopathological findings of 147 cases of T/NK-cell PTLD reported in the literature in an attempt to define subtype-specific characteristics. T/NK-cell PTLD occurs in patients of all ages, usually extranodally, and most frequently after kidney transplant. Organ specific incidence, however, is highest following heart transplant. Approximately one-third of T-cell PTLDs are Epstein–Barr virus (EBV)-related, with peripheral T-cell lymphoma, not otherwise specified (PTCL, NOS) being the most prevalent EBV-associated T-cell PTLD. A male predominance is observed, which is most striking in the EBV(+) group, particularly in PTCL, NOS. With a median posttransplant interval of 72 months, T-cell PTLDs are among the late-occurring PTLDs. Of the most common T-cell PTLDs, anaplastic large cell lymphoma (ALCL) has the best prognosis, whereas PTCL, NOS and hepatosplenic T-cell lymphoma (HSTCL) have the worst prognosis. EBV(+) cases seem to have a longer survival than EBV(−) cases, suggesting a different pathogenetic mechanism.